Simultaneous removal of SO2 and NOx from flue gas by wet scrubbing using a urea solution. Issue 20 (6th September 2019) - Li, Ge; Wang, Baodong; Xu, Wayne Qiang; Li, Yonglong; Han, Yifan; Sun, Qi
ABSTRACT: Nitrogen oxides (NOx ) and sulfur dioxide (SO2 ) are major air pollutants, so simultaneously removing them from gases emitted during fossil fuel combustion in stationary systems is important. Wet denitrification using urea is used for a wide range of systems. Additives have strong effects on wet denitrification using urea, and different mechanisms are involved and different effects found using different additives. In this study, the effects of different additives, initial urea concentrations, reaction temperatures, initial pH values, gas flow rates, and reaction times on the simultaneous desulfurization and denitrification efficiencies achieved using wet denitrification using urea were studied in single factor experiment. The optimum reaction conditions for desulfurization and denitrification were found. Desulfurization and denitrification efficiencies of 97.5% and 96.3%, respectively, were achieved at a KMnO4 concentration 5 mmol/L, a reaction temperature of 70°C, initial urea solution pH 8, a urea concentration of 9%, and a gas flow rate of 40 L/h. The concentrations of the desulfurization and denitrification reaction products in the solution were determined. NOx was mainly transformed into N2, and the NO 3 − and NO 2 − concentrations in the solution became very low. The reactions involved in SO2 and NOx removal using urea were analyzed from the thermodynamic viewpoint. Increasing the temperature was not conducive to the reactions but increased the rate constant, so an optimum temperature was determined. The simultaneous desulfurization and denitrification kinetics were calculated. The urea consumption and NO 2 −, NO 3 −, and SO 4 2 − generation reactions were all zero order. The NO 3 − generation rate was greater than the NO 2 − generation rate. The simultaneous desulfurization and denitrification process and mechanism were studied. The results provide reference data for performing flue gas desulfurization and denitrification in factories.